Shrī Kalagẖīdhara camatakāra, arathāta, Jīwana caritra sāhiba srī Gurū Gobinda Siṅgha jī - Wīra Siṅgha, Bhai (SAMP early 20th-century Indian books project, 1950)
Biography of Gobind Singh, 1666-1708, 10th guru of Sikhs.